Master of flood preparedness: Aware, prepare & resilient - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Noor Amira Syazwani, Abd Rahman; Ju, Soon Yew; Kong, Lai Kuan; Amirudin, Mohd Zani (Tiang Press, 2023)
In the face of nature's formidable power, humans have often found themselves vulnerable and ill-prepared. Within these virtual pages, you will find an interesting exploration of flood preparedness, ranging from the fundamental principles of flood dynamics to practical strategies for mitigation and recovery. Yet, this e-book is not merely a compilation of facts and figures. It serves as a call to action, urging each of us, especially youth to embrace the collective responsibility in building resilient communities. This e-book is designed with QR codes that facilitate convenient access to additional information on flood preparedness from primary sources. Moreover, it incorporates engaging and straightforward graphics to enhance reader comprehension of the book's contents. Despite its specific focus on enhancing the comprehension of the Master of Flood Preparedness (MOFP) players, this e-book has the potential to benefit the general public as well, fostering a greater understanding of flood preparedness.